ﺻﻮرة اﻟﺘﺸﺒﯿﮫ اﻟﻀﻤﻨﻲ ﻓﻲ ﺷﻌﺮ أﺑﻲ ﺗﻤﺎم. ت(. ٢٣١. )ھـ -دراﺳﺔ ﺗﺤﻠﯿﻠﯿﺔ (Journal of the College of Education for Women, 2019)
The research addresses a pattern of imagery which is regarded a Prominent feature of Abi Tamaam's Poetry (the image of implicit simile) which is based on the hidden signified and the signifier which can be deduced out of context . The investigation requires a study whose proof is based on imagery which is of three types: natural proof , human proof and Quran proof . After handling the realistic structures of this image, the researcher has shifted attention to its types and has dealt with the psychological domain , dividing it in two types: the sensory image and the mental image. The research is directed towards studying the implicit sentence regarding its styles of expression : declarative expression and composition expression . The research is directed towards studying the implicit sentence regarding its styles of expression : declarative expression and composition expression .